2019
DOI: 10.3389/fnins.2019.00591
|View full text |Cite
|
Sign up to set email alerts
|

Limited Benefit of Sleep Extension on Cognitive Deficits During Total Sleep Deprivation: Illustration With Two Executive Processes

Abstract: Introduction: Sleep extension has been associated with better alertness and sustained attention capacities before, during and after sleep loss. However, less is known about such beneficial effect on executive functions (EFs). Our aim was to investigate such effects on two EFs (i.e., inhibition and working memory) for subjects submitted to total sleep deprivation and one-night of recovery. Methods: Fourteen healthy men (26–37 years old) participated in an experimental cross-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…After a night of recovery sleep following sleep deprivation, alpha-band activation and functional connectivity did not return to normal levels, indicating that one night of sleep recovery cannot eliminate the damage caused by 36 of sleep deprivation. In general, sleep has a recovery and organizing effect on the cortical activity of wakefulness [56,57]. Although the sleep recovery effect was not signi cant in our results, the difference between RS and SD sessions was smaller than the difference between NS and SD sessions, thus con rming the homeostatic regulation of sleep to a certain extent [58].…”
Section: Discussionsupporting
confidence: 40%
“…After a night of recovery sleep following sleep deprivation, alpha-band activation and functional connectivity did not return to normal levels, indicating that one night of sleep recovery cannot eliminate the damage caused by 36 of sleep deprivation. In general, sleep has a recovery and organizing effect on the cortical activity of wakefulness [56,57]. Although the sleep recovery effect was not signi cant in our results, the difference between RS and SD sessions was smaller than the difference between NS and SD sessions, thus con rming the homeostatic regulation of sleep to a certain extent [58].…”
Section: Discussionsupporting
confidence: 40%
“…After a night of recovery sleep following sleep deprivation, alpha-band activation and functional connectivity did not return to normal levels, indicating that one night of sleep recovery cannot eliminate the damage caused by 36 h of sleep deprivation. In general, sleep has a recovery and organizing effect on the cortical activity of wakefulness 30 , 53 . Although the sleep recovery effect was not significant in our results, the difference between RS and SD sessions was smaller than the difference between NS and SD sessions, thus confirming the homeostatic regulation of sleep to a certain extent 54 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study demonstrated that six nights of sleep extension before sleep deprivation did not reduce inhibition control deficits during a total sleep deprivation period. 18 By contrast, another study found that six nights of sleep extension was sufficient to reduce vigilant attention deficits related to total sleep deprivation. 82 Therefore, the effects of sleep deprivation on inhibition control likely depend on the interaction of vigilant attention, working memory, decision making, and sensory perception, among other factors.…”
Section: Discussionmentioning
confidence: 95%
“… 14 In another study in which 12 participants spent 14 days in the laboratory with 2 baseline days followed by 7 days of partial sleep restriction and 3 recovery days, researchers observed a significant sleep restriction effect on errors of commission in the Go/No-Go task. 18 However, a few studies have found no significant changes in individuals’ levels of inhibition control after TSD or PSR. 23 , 28 , 41 For example, some researchers posit that sleep deprivation does not affect inhibition per se, but rather affects a supervisory attentional process, which is regarded as an active effort to cope with a complex task.…”
Section: Discussionmentioning
confidence: 99%